2006
DOI: 10.1682/jrrd.2005.01.0014
|View full text |Cite
|
Sign up to set email alerts
|

Treatability of different components of aphasia--Insights from a case study

Abstract: Abstract-In this phase I clinical rehabilitation study, we investigated the effects of phonological rehabilitation for alexia and aphasia in an individual 54 years after a left-hemisphere ischemic infarction. In the context of a single-subject design, we studied whether treatment would improve phonological processing, reading, and generalization to untreated behaviors. While results showed a lack of generalization to real-word reading aloud, improvement was present in phonological processing, language function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Studies examining recovery in aphasia show that most spontaneous recovery actually occurs within the first 2 months post-aphasia onset (e.g., Holland, Greenhouse, Fromm, & Swindell, 1989). Although treatment effects are greatest in acute stages of aphasia recovery, several studies have reported remarkable gains in language abilities many years following aphasia onset (e.g., Kendall et al, 2006).…”
Section: Timing Of Treatment Deliverymentioning
confidence: 99%
“…Studies examining recovery in aphasia show that most spontaneous recovery actually occurs within the first 2 months post-aphasia onset (e.g., Holland, Greenhouse, Fromm, & Swindell, 1989). Although treatment effects are greatest in acute stages of aphasia recovery, several studies have reported remarkable gains in language abilities many years following aphasia onset (e.g., Kendall et al, 2006).…”
Section: Timing Of Treatment Deliverymentioning
confidence: 99%
“…The BNT is a standardized naming test that has been normed on several populations, published as a shortened version, and translated into several languages (e.g., Pedraza et al, 2009; Kohnert et al, 1998; Mack et al, 1992; Tombaugh and Hubley, 1997). The BNT has been used extensively as an outcome measure in clinical studies (e.g., Kendall et al, 2006; Naeser et al, 2010) and thus, understanding its neural underpinnings would add significant clinical value.…”
mentioning
confidence: 99%
“…Some of these programs already exist, though in a very different place than we might expect: therapies for aphasic patients, who are unable to use entire cognitive routes, have been designed to support or develop various processes damaged by illness. Certain components from these could be incorporated into EFL policy, or at least be evaluated for the way they target specific cognitive activities or practices (Beeson et al., ; Greenwald, ; Kendall et al., ). Of course, these should only be considered by planners following their own programmatic needs analyses, after discussion with other planners, researchers, cognitive scientists, and even medical doctors conducting research into the human brain and language‐related phenomena.…”
Section: Implications and Recommendationsmentioning
confidence: 99%